Casting doubt on the value of assessing the cardiac index in pregnancy*. (2nd December 2018) - Ram, Maya; Lavie, Anat; Lev, Shaul; Blecher, Yair; Amikam, Uri; Shulman, Yael; Avnon, Tomer; Weiner, Eran; Many, Ariel
Abstract: Objectives: The objective of this study is to assess the reliability of the cardiac index (CI) in healthy pregnant women at term by investigating the correlation between the cardiac output (CO) and the body surface area (BSA) using a novel non-invasive cardiography technique (NICaS™). Methods: Sixty-one healthy, normotensive women with a singleton pregnancy at term (≥37 gestational weeks) participated in this prospective observational study between 1/2015 and 6/2015 L. Each woman was assessed for CO by the NICaS™, an impedance device that non-invasively measures the CO and its derivatives. The NICaS™ demonstrated a very good correlation with the gold standard Swan–Ganz catheter. BSA was determined by the Dubois nomogram. Results: The mean ± standard deviation maternal age was 34.2 ± 5.3 years, mean height 166 ± 6 cm, and mean body mass index 23.9 ± 4.9 kg/m 2 . The mean gestational age was 38.8 ± 0.7 weeks. The correlation between the CO and the BSA was poor (Pearson r = 0.254, p < .005). Conclusions: The current study demonstrated poor correlation between the CO and the BSA in pregnant women, therefore, making the CI a non-reliable variable for assessing CO in pregnant women. We, therefore, suggest that the CO rather than the CI is the preferred parameter for hemodynamic measurements in this population.